Pan-cancer analysis of genomic scar patterns caused by homologous repair deficiency (HRD) - Rempel, Eugen; Kluck, Klaus; Beck, Susanne; Ourailidis, Iordanis; Kazdal, Daniel; Neumann, Olaf; Volckmar, Anna-Lena; Kirchner, Martina; Goldschmid, Hannah; Pfarr, N.; Weichert, Wilko; Hübschmann, Daniel; et al. (npj precision oncology, 2022)
Homologous repair deficiency (HRD) is present in many cancer types at variable prevalence and can indicate response to platinum-based chemotherapy and PARP inhibition. We developed a tumor classification system based on the loss of function of genes in the homologous recombination repair (HRR) pathway. To this end, somatic and germline alterations in BRCA1/2 and 140 other HRR genes were included and assessed for the impact on gene function. Additionally, information on the allelic hit type and on BRCA1 promoter hypermethylation was included. The HRDsum score including LOH, LST, and TAI was calculated for 8847 tumors of the TCGA cohort starting from genotyping data and for the subcohort of ovarian cancer also starting from WES data. Pan-cancer, deleterious BRCA1/2 alterations were detected in 4% of the tumors, while 18% of the tumors were HRD-positive (HRDsum ≥ 42). Across 33 cancer types, both BRCA1/2 alterations and HRD-positivity were most prevalent in ovarian cancer (20% and 69%). Pan-cancer, tumors with biallelic deleterious alterations in BRCA1/2 were separated strongly from tumors without relevant alterations (AUC = 0.89), while separation for tumors with monoallelic deleterious BRCA1/2 alterations was weak (AUC = 0.53). Tumors with biallelic deleterious alterations in other HHR genes were separated moderately from tumors without relevant alterations (AUC = 0.63), while separation for tumors with such monoallelic alterations was weaker (AUC = 0.57). In ovarian cancer, HRDsum scores calculated from WES data correlated strongly with HRDsum scores calculated from genotyping data (R = 0.87) and were slightly (4%) higher. We comprehensively analyzed HRD scores and their association with mutations in HRR genes in common cancer types. Our study identifies important parameters influencing HRD measurement and argues for an integration of HRDsum score with specific mutational profiles.